What Kind of Learning Media do You Want? Need Analysis On Elementary School Online Learning - Utomo, Gatot Margisal; Setiawan, Bramianto; Rachmadtullah, Reza; Iasha, Vina (Jurnal Basicedu, 2021)
This preliminary research was conducted to find information on learning media that teachers and students want in online learning. The qualitative descriptive research method is applied in this study. The study was conducted in August 2021. The study was conducted in an elementary school in both urban and rural areas. A total of 105 people were interviewed at the school, including teachers and students. The data collection technique was carried out through a survey using a google questionnaire form which was divided into 2 forms, namely forms for teachers and students. The findings of the teacher survey indicate that learning media is needed to provide students with a realistic picture of phenomena in online learning. By providing interactive learning media, students feel it will be easier to understand the material than just being explained or given assignments. On the other hand, the results of student questionnaires also indicate that they want learning media in the online learning process. learning media that can convey the topic so that students can see the phenomenon.